ERROR ANALYSIS ON ENGLISH WRITING SKILL FOR THE SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Mukhlasul Fasikh; Abdul Muhid Murtadho (STIBA IEC JAKARTA, 2019)
This study aims to know the variety of errors, the most typical error and the least typical error on grammar writing for the grade students in the state of junior high school 5 Setu, and also to make teaching and learning activities more effective and efficient. This research is descriptive research method. The research instrument in this research is writing task. Writer uses the questioners to collect the data. Students answer the questions and from the answers’ students are arranged to be paragraph. The discussion of the errors are frequently occurred in the students’ English writing capitalization have the high percentage 12.93%, punctuation 12.93%, spelling form 12.50%, word form 11.21%, singular-plural 10.34%, article 9.48%, present tense 8.62%, added word 8.62%, word choice 7.33%, preposition 4.31%, and omission 1.72%. By studying the percentage of the error analysis on English writing skill, the writer found the ability of the students in writing skill was neither too low nor too high. The most typical error is on capitalization (12.93%) and the least typical error is on omission (1.72%)